Penggunaan Gadget Untuk Meningkatkan Kemampuan Mengolah Informasi Siswa - Maesaroh, Nur Siti; Yulifar, Leli (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2024)
This research is based on findings from class XI IPS in SMA Pasundan 2 Bandung, which shows a low level of student skills in processing information. To resolve the issue, researchers are implementing the use of gadgets to enhance student skills in processing information. The goal of this research is to enhance student skills in processing information during history lessons. This research uses Action Research methodology. The results of the research from the first cycle, second cycle, and third cycle show a significant increase. In the first cycle, the students' ability to process information was still low. This was due to the students' lack of optimizing their use of gadgets in searching for information, using unreliable sources, and not being able to interpret information in their own language. In the second cycle, a significant improvement occurred in all three indicators. In the third cycle, the students fully utilized their gadgets to search for information and did not rely on a single source of information. They used credible sources of information, interpreted the information in their own language, and presented the information in a concise, dense, and easily understandable manner using infospace media. With the results of this research, it is hoped that relevant parties can develop and improve the learning process of history through the use of gadgets.